Identification of Nontuberculous Mycobacterium and Mycobacterium tuberculosis Complex in Sputum Patients with Suspected Tuberculosis - Fanny Indriyani Biyang; Muhammad Nasrum Massi; Lisa Tenriesa Muslich; Andi Rofian Sultan; Mochammad Hatta; Ahmad Rahmat Ramadhan; Baedah Madjid (International Journal of Mycobacteriology)
Background: Pulmonary tuberculosis (TB) is predominantly caused by Mycobacterium tuberculosis complex (MTBC) and can also involve nontuberculous mycobacteria (NTM). These pathogens pose significant global health challenges, particularly in developing countries. Differentiating between MTBC and NTM in clinical specimens is often difficult using conventional acid-fast staining methods, leading to an underestimation of NTM prevalence in TB-endemic regions. This study aims to identify mycobacterial species in sputum samples from patients suspected of having TB, utilizing polymerase chain reaction (PCR) assays and gene sequencing techniques. Methods: We collected 111 sputum samples from patients at Dr. Wahidin Sudirohusodo Central General Hospital, Hasanuddin University Hospital, and Makassar Community Lung Health Center. The samples were analyzed at the Clinical Microbiology Laboratory of Hasanuddin University using standard microscopy and molecular detection techniques. Descriptive statistics were employed to summarize patient demographics, infection characteristics, and outcomes. Results: We collected sputum from suspected TB patients with an average age of 50.86 years. We found 16.2% (n = 18) acid-fast bacteria in 111 patients with suspected pulmonary TB, and molecularly, we identified 17.1% (n = 19) Mycobacterium species by multiplex PCR. Three sputum samples tested positive for NTM. Phylogenetic analysis, based on 16S rRNA gene sequencing, revealed similarities between the samples and known mycobacterial species. Conclusions: The study underscores the challenges in differentiating between MTBC and NTM, highlighting the necessity for molecular diagnostic approaches. Notably, we found NTM in sputum samples from patients previously treated for TB. These findings can serve as a reference for improving diagnostic accuracy and preventing misdiagnosis of mycobacterial infections.